2020
DOI: 10.1093/nargab/lqaa016
|View full text |Cite
|
Sign up to set email alerts
|

Joint single cell DNA-seq and RNA-seq of gastric cancer cell lines reveals rules of in vitro evolution

Abstract: Cancer cell lines are not homogeneous nor are they static in their genetic state and biological properties. Genetic, transcriptional and phenotypic diversity within cell lines contributes to the lack of experimental reproducibility frequently observed in tissue-culture-based studies. While cancer cell line heterogeneity has been generally recognized, there are no studies which quantify the number of clones that coexist within cell lines and their distinguishing characteristics. We used a single-cell DNA sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
124
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(135 citation statements)
references
References 37 publications
11
124
0
Order By: Relevance
“…Single-cell RNA sequencing (scRNA-seq) technology has been used to identify the subpopulations of a range of cancers, including hematopoietic ( Jaitin et al, 2014 ), pancreatic ( Peng et al, 2019 ), liver ( Halpern et al, 2017 ), colorectal ( Dai et al, 2019 ), and lung cancers ( Kim et al, 2020 ). Moreover, single-cell DNA sequencing (scDNA-seq) is also useful for the discovery of copy-number ( Gao et al, 2016 ; Laks et al, 2019 ) and branching evolution in cancers ( Yu et al, 2014 ; Wang et al, 2017 ; Andor et al, 2020 ). Recently, single-cell-based transcriptomics or epigenomics have been applied to deconstruct heterogeneity present within hPSC-derived brain organoids ( Tanaka et al, 2020 ) and kidney organoids ( Wu and Humphreys, 2020 ; Subramanian et al, 2019 ).…”
Section: Applications Of Hpsc-based Cancer Modelingmentioning
confidence: 99%
“…Single-cell RNA sequencing (scRNA-seq) technology has been used to identify the subpopulations of a range of cancers, including hematopoietic ( Jaitin et al, 2014 ), pancreatic ( Peng et al, 2019 ), liver ( Halpern et al, 2017 ), colorectal ( Dai et al, 2019 ), and lung cancers ( Kim et al, 2020 ). Moreover, single-cell DNA sequencing (scDNA-seq) is also useful for the discovery of copy-number ( Gao et al, 2016 ; Laks et al, 2019 ) and branching evolution in cancers ( Yu et al, 2014 ; Wang et al, 2017 ; Andor et al, 2020 ). Recently, single-cell-based transcriptomics or epigenomics have been applied to deconstruct heterogeneity present within hPSC-derived brain organoids ( Tanaka et al, 2020 ) and kidney organoids ( Wu and Humphreys, 2020 ; Subramanian et al, 2019 ).…”
Section: Applications Of Hpsc-based Cancer Modelingmentioning
confidence: 99%
“…To identify clonal CNVs, we performed whole genome single cell sequencing on a subset of four mCRC samples (P5915, P6593, P6335 and P6198). We modeled per-cell read counts per genomic bin as a Poisson distribution dependent on both the GC content and the copy number as previously described (Andor et al 2020), using Cell Ranger. The GC bias was modeled as a quadratic function with fixed intercept and correction on a cell-by-cell basis was performed.…”
Section: Influence Of Copy Number Variation On Tumor Heterogeneitymentioning
confidence: 99%
“…cellular state) of resident cells for any given tumor (Lim et al 2020;Sathe et al 2020). Single cell DNA sequencing studies have revealed a broad spectrum of genomic alterations such as copy number variation that distinguishes different clonal populations (Leung et al 2017;Andor et al 2020;Velazquez-Villarreal et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Such events include the pervasively occurring copy-neutral loss of heterozygosity (LOH) [5][6][7][8] , intriguing "mirrored events" 9,10 where a given tumor may have cancer cells carrying amplification of one haplotype are intermingled with cancer cells carrying amplification of the other haplotype, and the even more complex alterations that are only detectable through allele-specific analysis 11 . While the importance of allelespecific copy number has been emphasized in bulk DNA sequencing analysis [5][6][7][8]11 , most single-cell CNV analysis considers only total copy number due to low per-cell coverage [12][13][14][15][16][17][18][19] . Recently, Zaccaria et al developed CHISEL 10 , a method for single-cell allele-specific copy number analysis, but requires externally phased haplotypes based on large reference cohorts.…”
Section: Introductionmentioning
confidence: 99%